Cancer stem cell dynamics in tumor progression and metastasis: Is the microenvironment to blame? - Fessler, Evelyn; Dijkgraaf, Feline E.; De Sousa E Melo, Felipe; Medema, Jan Paul (Cancer letters, 2013)
► Like normal tissues, cancerous tissues are organized hierarchically. ► The hierarchy in cancer is more dynamic with the possibility of reversion. ► The hierarchy and its reversion can be orchestrated by the microenvironment. ► CSCs and their niche cells are important for tumor progression and metastasis. Stem cells are defined by their self-renewal capacity and the ability to give rise to all differentiated progeny necessary for one specific organ. These two characteristics are also inherent in cancer stem cells (CSCs), which are thought to be the only subpopulation within a tumor endowed with tumorigenic potential. CSCs combine many features that render cancer one of the leading causes of death in the Western world: metastasis, tumor recurrence, and therapy refractoriness. Strikingly, CSCs are not a fixed entity, but differentiated tumor cells are able to revert to a stem-like state. Thus, CSCs are not only intrinsically programmed to fulfill their detrimental roles, but are orchestrated by stromal cells residing in their vicinity and forming the CSC niche. Yet, this relationship is not a one-way road: CSCs are able to manipulate stromal cells to their needs, not only in the primary tumor, but also in distant organs and thus prime the foreign soil for their arrival by inducing a premetastatic niche. The suggested plasticity between the differentiation states of cancer cells and the regulation by microenvironmental cues provides new starting-points for novel cancer therapies.